Micromechanics modeling and validation of thermal-mechanical damage in DER353 epoxy/borosilicate glass composite subject to high strain rate deformation - Li, Zhiye; Ghosh, Somnath (International journal of impact engineering, 2020)
•This study presents a new multi-physics model that captures the mechanical performance of fiber-reinforced polymer composite materials subjected to high-speed impacts.•A thermal-mechanical Epoxy model, calibrated from SHPB, elucidates the mechanism of damage evolution and energy conversion in high-rate problems.•In the micromechanical model, all single-phase damage and interfacial debonding are affected by stress-wave propagation.•The model established in this paper is validated by comparison with a unidirectional fiber punch shear experiment. With advances in the design and manufacturing of composite materials, the number of their defense and civil applications has grown significantly. This calls for detailed experiments and modeling of composite materials for their characterization and performance analysis. Experiments show that adiabatic heating becomes more noticeable at high-strain-rate deformation, causing the stress-strain slopes to become negative. However, most rate-dependent micromechanics models, e.g. in a previous work by the authors [1], lack an interpretation of the relation between energy dissipation and adiabatic temperature rise. In this study, a continuum damage model (CDM) with adiabatic heating is established to enhance the accuracy of the micromechanics model under high-strain-rate impacts. The model predicts the behavior of a heterogeneous material and punch shear strength tests are used for validation. The model is calibrated using results from experiments conducted in a split-Hopkinson pressure bar (SHPB). A constitutive law for the DER353 epoxy in the finite rotation framework is presented first, focusing on the connection between the energy dissipation and local temperature rise. Next, the model is implemented in a finite element framework and calibrated using a SHPB experiment. Lastly, the DER353 epoxy model is applied to a unidirectional fiber composite micromechanics model as a predictive tool. Results show that damage initiates at the material interface and diffuses into individual phases. In addition, the punch shear experiment results are compared with results from the single-fiber RVE model. The comparison shows that the micromechanical model can be used as a multiscale analysis tool. The findings in this work can be used to explore the performance of more complicated microstructures, e.g. woven composites.